Case Study of a Farmer Producer Organization : Bhangar Vegetable Producer Company Limited - Kundu, Prasenji; Ghosh, Sarba Swarup; Sahu, Narayan Chandra (Journal of Agricultural Extension Management, 2022)
A Farmer Producer Organization enables the farming community, including the small and marginal farmers, in addressing their Production and Marketing issues. Many Producer Companies have come up in India as well as in West Bengal to address these concerns. In this context, one successful Farmer Producer Company (FPC) i.e. Bhangar Vegetable Producer Company was selected from West Bengal which produces diverse kinds of products and a comparative study has been made to document the factors responsible for success which can act as guiding factors for other FPCs. This Company has minimized the production risks and marketing risks. They have taken initiative in post-harvest processes which ultimately ensured higher income. The success of a Producer Company needs to be judged on the basis of benefits accruing to the farmers.